Severe Focal Sialadenitis and Dacryoadenitis in NZM2328 Mice Induced by MCMV: A Novel Model for Human Sjögren’s Syndrome - Ohyama, Yukiko; Carroll, Virginia A.; Deshmukh, Umesh; Gaskin, Felicia; Brown, Michael G.; Fu, Shu Man (The Journal of immunology (1950), 2006)
The genetic and environmental factors that control the development of Sjögren’s syndrome, an autoimmune disease mainly involving the salivary and lacrimal glands, are poorly understood. Viruses which infect the glands may act as a trigger for disease. The ability of sialotropic murine CMV (MCMV) to induce acute and chronic glandular disease was characterized in an autoimmune-prone mouse strain, NZM2328. MCMV levels were detectable in the salivary and lacrimal glands 14–28 days after i.p. infection and correlated with acute inflammation in the submandibular gland. After latency, virus was undetectable in the glands by PCR. At this stage, NZM2328 female mice developed severe chronic periductal inflammation in both submandibular and lacrimal glands in contrast to the much milder infiltrates found in female B6-lpr and male NZM2328. The focal infiltrates consisted of CD4+ and B220+ cells as opposed to diffuse CD4+, CD8+, and B220+ cells during acute infection. Salivary gland functional studies revealed a gender-specific progressive loss of secretory function between days 90 and 125 postinfection. Latent MCMV infection did not significantly affect the low incidence of autoantibodies to Ro/SSA and La/SSB Ags in NZM2328 mice. However, reactivities to other salivary and lacrimal gland proteins were readily detected. MCMV infection did not significantly alter the spontaneous onset of kidney disease in NZM2328. Thus, chronic inflammation induced by MCMV with decreased secretory function in NZM2328 mice resembles the disease manifestations of human Sjögren’s syndrome.